Sacrilegious heroics: Biblical and Byronic archetypes of the vengeful feminine - Camilleri, A (Liverpool University Press, 2015)
That Byron possessed an abiding interest in the active individuality of women is manifest in his poetry. From the opening canto of Childe Harold’s Pilgrimage to the closing cantos of Don Juan, examples of female independence and autonomy abound. Next to the heroines of Homer, Virgil, and Shakespeare, Biblical female exploits provide a powerful catalogue of heroic endeavour—with which Byron was undoubtedly familiar, and from which he likely drew. Though manifold Biblical instances of female fortitude may find parallels in Byron’s work, this article will contemplate one particular Biblical/Byronic pair: Judith and Gulnare. In this article, I suggest that The Book of Judith provides a possible source through which we might contemplate Byron’s examination of female vengeance and the gendered dynamics of violence.